2023
DOI: 10.1093/rb/rbad011
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-modified bone cement promotes osteoporotic bone defect repair in ovariectomized rats by restoring GPx1-mediated mitochondrial antioxidant functions

Abstract: Over-accumulation of reactive oxygen species (ROS) causes mitochondrial dysfunction and impairs the osteogenic potential of bone marrow-derived mesenchymal stem cells (BMMSCs). Selenium (Se) protects BMMSCs from oxidative stress-induced damage; however, it is unknown whether Se supplementation can promote the repair of osteoporotic bone defects by rescuing the impaired osteogenic potential of osteoporotic BMMSCs (OP-BMMSCs). In vitro treatment with sodium selenite (Na2SeO3) successfully improved the osteogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Evidence suggests that FLNA is involved in negatively regulating osteogenesis and positively modulating osteoclastogenesis [ 39 ]. Loss of NUBPL function triggers mitochondrial dysfunction [ 40 ], which could disrupt both bone formation and resorption [ 41 ]. Importantly, the present study confirmed that the disulfidptosis regulators ACTB, FLNA, and NUBPL exhibited lower expression levels in OP samples, thus influencing disulfidptosis processes in OP.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that FLNA is involved in negatively regulating osteogenesis and positively modulating osteoclastogenesis [ 39 ]. Loss of NUBPL function triggers mitochondrial dysfunction [ 40 ], which could disrupt both bone formation and resorption [ 41 ]. Importantly, the present study confirmed that the disulfidptosis regulators ACTB, FLNA, and NUBPL exhibited lower expression levels in OP samples, thus influencing disulfidptosis processes in OP.…”
Section: Discussionmentioning
confidence: 99%
“…8-week-old male Sprague-Dawley (SD) rat BMSCs were extracted with reference to previous studies ( Zhou et al, 2023 ). Rat BMSCs were cultured using modified α-minimum medium (containing 10% fetal bovine serum, 1% penicillin, and streptomycin) at 37°C in an environment of 5% carbon dioxide.…”
Section: Methodsmentioning
confidence: 99%
“…The isolation of rat BMMSCs was conducted using 8-week-old Sprague Dawley (SD) rats in accordance with a previously reported protocol [ 22 ]. Specifically, after sacrificing, the rat femurs and tibias were collected.…”
Section: Methodsmentioning
confidence: 99%